2012
DOI: 10.7166/16-2-167
|View full text |Cite
|
Sign up to set email alerts
|

A Zero Sampling Plan for the Moderation of Examination Papers

Abstract: Quality assurance within local educational institutions has been under the spotlight in recent years. In particular these institutions are increasingly subjected to minimum standards specified by controlling bodies such as the Higher Education Quality Committee and others. The moderation of examination papers is an important quality assurance activity to ensure that an examination paper's standard, content, span and marking are fair and reasonable. This paper describes a sampling plan to determine the number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 3 publications
0
4
0
1
Order By: Relevance
“…the standard). If C is forced not to exceed zero (C=0) the sampling plan defaults to the zero sampling plan discussed in [7], and it can be shown that the above inequality reduces to equation (10) in [7]. The reader will also notice that if the entire set of books is moderated (k=s), then the acquired confidence is 100% (which of course must be the case).…”
Section: Total (C)mentioning
confidence: 99%
See 4 more Smart Citations
“…the standard). If C is forced not to exceed zero (C=0) the sampling plan defaults to the zero sampling plan discussed in [7], and it can be shown that the above inequality reduces to equation (10) in [7]. The reader will also notice that if the entire set of books is moderated (k=s), then the acquired confidence is 100% (which of course must be the case).…”
Section: Total (C)mentioning
confidence: 99%
“…2 The uniform distribution was used for no other reason than its simplicity. During the analysis of the zero sampling plan [7] it was found that the form and parameters of this prior distribution have a relatively small effect on the results. It appeared that the knowledge obtained about the specific examiner during the moderation of the sample and captured by the process of Bayesian statistics contained much more information than the prior assumption about the population to which the examiner belongs.…”
Section: Derivation Of the Theory For The Non-zero Sampling Planmentioning
confidence: 99%
See 3 more Smart Citations